"Honour" killings in Europe as an effect of migration process: perspective for Poland - Sadowa, Katarzyna (2015)
In this paper the author analyses the phenomenon of so-called honour killings as an actual problem of European countries. The author shows that the issue is present in Europe as the result of immigration process and simultaneity is far from resolving. Moreover, while there is a great risk of its' increase, the proper combating measures are needed. As the author comes from Poland, the main aim of the publication is to stress that the problem of "honour" killings and wider - "honour" based violence is a growing threat to this country. Therefore, adequate strategy preventing the issue should be prepare now. Firstly, the author shortly characterizes the issue by providing proper definition and demonstrates its scale. The of the actual problem of "honour" killings in Europe is described especially by analysing the causal link between the immigration process and honour based violence. The second part of the publication contains the analysis of United Kingdom's strategy for fighting again